Current Perspective to Predict Actual Evapotranspiration - Bucur, Daniel (IntechOpen, 2017)
Evapotranspiration is the largest outgoing water flux from the Earth's surface; its accurate quantification is critical for the crop development in conditions of the climate changes from recent decades, and it can contribute to a greater understanding of a range of agricultural ecosystem processes. To evaluate the hydric requirements of the crops, it was agreed that they should be reported to a maximum global evapotranspiration called potential evapotranspiration. To estimate this variable, a variety of methods were developed, each with its benefits as well as trade-offs. Their use, however, is laborious due to their complexity and of the large number of parameters required. In this book, specialists' concerns worldwide to develop simple but reliable methodologies - with less data requirement - which will give accurate and appropriate results - are presented. In addition, a study of the physics of the moisture evaporation process from porous media to elucidate what are the mechanisms of moisture migration from granular biopesticides is presented in the last chapter.